PERLINDUNGAN HUKUM BAGI WAJIB PAJAK DALAM PENYELESAIAN SENGKETA PAJAK - Rochaeti, Etty (Jurnal Wawasan Yuridika, 2012)
In the legal protection to tax payers in tax dispute, there is a legal effort which has been accommodated and provided by Act of Tax, both outside and through tax judicature. The protection outside the tax judicature, can be in the forms of proposal to the change of miswriting and miscalculation performed by tax payers, or tax officials is wrong to publish the tax provision, so the tax payers ask for the correction of the tax provision. The law protection through tax judicature can be in the form of proposal of objection to the Board of Objection, accusation to Tax of Court of Justice, judicial review from the Supreme Court. The substance of law related to law protection to tax payers in the tax dispute settlement, there is no legal norm synchronization. The legal effort for tax payers in looking for justice is missing because there are provisions of article 33 paragraph (1) and article 77 paragraph (1), Act No. 44 year of 2014 which state that the decision of Tax Court of Justice is a final decision in examining and deciding the tax dispute, so there is no more accusation and appeal to the Supreme Court. The legal effort which is permitted is through performing judicial review, and its legal effort is extraordinary. The relative competency of Tax Court of Justice covers the whole area of Indonesia.Keywords: law protection, tax payers.